The role and main directions of mobile devices in modern education - Makhkamov, Farkhod; Mukhamedjonova, Zukhra (MMIT Proceedings, 2024)
Conclusion. In the future, teachers and students of higher education institutions should not be limited by the opportunity to study and receive education at a certain place and time. In the near future, mobile devices and wireless technologies will become an everyday part of learning both inside and outside the classroom. The majority of modern students are technically and psychologically ready to use mobile technologies in education, and it is necessary to consider new opportunities to use the potential of mobile education more effectively. The solution to this problem is the organizational effort of scientists and teachers in education, research and methodical work on the implementation of mobile education strategies, forms and methods in the educational process of higher education institutions. requires action.